Measuring The Quality Of Life (QoL) Of Villagers In Pulau Tuba, Langkawi - Siti Khadijah Abd Manan; Rafeah Saedon; Amiratul Munirah Yahaya; Mohd Hafiz Abd Wahab (USIM Press, 2024)
VOL. 28 NO. 2 Page (193-204)